The concept of insurance and its role in the global space insurance (Journal of actual problems of jurisprudence, 2019)
Insurance rick and insurance activity is an economic category of protecting the interests of insurers andinsured’s and expresses the interests of the parties. Of people protection and the wealth and in general, andit is a degree of the development of human rights.Keywords: insurance, compulsory insurance, insurance relations, insurance companies.